1993
DOI: 10.1111/j.1600-0714.1993.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent aphthous ulceration: a possible clinical manifestation of reactivation of varicella zoster or cytomegalovirus infection

Abstract: The etiology of the most common intraoral mucosal disease, recurrent aphthous ulceration (RAU), remains obscure. Here, attempts were made to diagnose reactivation of varicella zoster (VZV), cytomegalovirus (CMV), Epstein-Barr (EBV) and human hepes virus 6 (HHV-6) infections from paired sera in association with RAU recurrences. The first sample was obtained within 3 days after a new recurrence (1) and the second 10-14 days later (2). The study initially comprised 18 otherwise healthy RAU patients (gr A) and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 18 publications
0
36
1
3
Order By: Relevance
“…Oral streptococci have been suggested as important determinants of RAS, either as direct pathogens or as an antigenic stimulus culminating in the genesis of antibodies that may cross-react with keratinocyte antigenic determinants [39–41]. Helicobacter pylori [42, 43], herpes viruses [4446], Varicella zoster virus [47], and cytomegalovirus [47, 48] have also been implicated in RAS. Our study could not analyze the associations between these factors and OAUs because of a lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…Oral streptococci have been suggested as important determinants of RAS, either as direct pathogens or as an antigenic stimulus culminating in the genesis of antibodies that may cross-react with keratinocyte antigenic determinants [39–41]. Helicobacter pylori [42, 43], herpes viruses [4446], Varicella zoster virus [47], and cytomegalovirus [47, 48] have also been implicated in RAS. Our study could not analyze the associations between these factors and OAUs because of a lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…HSV virons and antigens have neither been identified in aphthous lesions nor successfully isolated in RAS biopsy tissues 20,21 . Although it has been suggested that reactivation of varicella zoster virus (VZV) or human cytomegalovirus (CMV) is associated with frequent recurrence of aphthous ulcers 22 , evaluation of RAS biopsy tissue using polymerase chain reaction (PCR) for possible involvement of HV6, CMV, VZV, Epstein-Barr virus (EBV), as causative factors did not find evidence to support the role of these viruses in RAS pathogenesis 20,23 . Thus, it is the clinician's responsibility to distinguish RAS from herpes infections, reassure RAS patients that they do not have an infectious disease and that antiviral therapy is neither necessary nor effective.…”
Section: Microbial Factorsmentioning
confidence: 99%
“…Only about a third of RAS patients are HSV-seropositive (Ship et al, 1967), and HSV (Studd et al, 1991). IgM and IgG antibodies to varicella zoster virus (VZV) may be elevated in some RAS patients (Pedersen and Hornsleth, 1993), suggesting an association between reactivation of VZV and RAS. Furthermore, VZV DNA can be detected in lesional tissue by the polymerase chain-reaction ; however, contamination is possible and may underlie these observations (Pedersen etal., 1993).…”
Section: Microbial Aspects Of Rasmentioning
confidence: 99%
“…Antibodies to cytomegalovirus (CMV) may be significantly elevated in some RAS patients (Pedersen and Hornsleth, 1993), and CMV DNA has been detected in illdefined oral ulcerations in non-HIV-infected persons (Leimola-Virtanen et al, 1995).…”
Section: Microbial Aspects Of Rasmentioning
confidence: 99%